Sperm recovery and IVF outcome after surgical sperm retrieval in azoospermia: our experience - Rai, Seema; Rao, P. S.; S., Prajwal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In the last decade, male factor infertility has been recognized as a significant global problem, which is on an increase. Till date, very few options are available for ameliorating male factor infertility. Development of intracytoplasmic sperm injection has revolutionized the treatment of males with very low sperm counts or with poor quality sperm. However, patients with a diagnosis of azoospermia had no option but to resort to adoption or use of donor sperm. The clinical management of men with azoospermia seeking fertility has been a challenge for andrologists, urologists, and reproductive medicine specialists alike. The older approaches denied such couple the possibility of having own genetic children. Surgical sperm retrieval and intracytoplasmic sperm injection have successfully transformed the treatment of male infertility so that now most of the men can father their own children. The aim of this study is to present the outcome of IVF with surgically retrieved sperm from azoospermic men. Methods: This study was a retrospective analysis of 100 cycles using surgically retrieved sperm. Outcome measures were fertilization rate (FR) and implantation rate (IR) per transfer. Results: Sperm retrieval rate in our study was 76% when Per cutaneous epididymal sperm aspiration (PESA) and Testicular sperm extraction (TESE) are combined. Our data demonstrated similar outcome between the use of epididymal or testicular sperm in men with azoospermic. There was no statistical difference concerning fertilization rate, embryo quality and pregnancy rate between ICSI with surgically retrieved sperm and ejaculated sperms. Conclusions: Surgical sperm retrieval is a feasible and successful procedure. Spermatozoa can be retrieved from the testis in up to 76% of patients, even in cases with severe disorders of spermatogenesis and deranged hormonal profile. Comprehensive genetic counseling is important for infertile couples deciding for surgical sperm retrieval, since genetic disorders, as yet undetected, may be passed on to the following generation with multiplying variety.